High-Resolution Spectroscopy through Tunable, Ultrastable Optical Radiation Diode Laser - Prasad Brij Mohan Kumar (MATEC Web of Conferences, 2016)
We report onthe combination of good tunability with superb short-term frequency, stability and controllability which exhibits the excellent spectral properties of a diode laser set up. The concept of this is based on merging of the diode laser with resonant optical feedback and the grating stabilized diode laser. The short-term performance to characterize it is batted two essentially identical diode lasers also to find short-term line width. Between these lasers phase locking is achieved with a servo small bandwidth although it is required for subradian residual phase error to use of an analog phase detector. The concept of the laser is suitable for atomic or molecular coherence experiments only due to the excellent performance.